CSR and local conflicts in African mining communities. (October 2022) - Bezzola, Selina; Günther, Isabel; Brugger, Fritz; Lefoll, Erwin
Highlights: One-quarter of mining operations in Africa face social conflicts in nearby communities. This paper analyses the impact of Corporate Social Responsibility (CSR) spending on conflict. The higher the risk of conflict, the more likely it is that companies engage in CSR spending. At least in the short term, this functional use of CSR reduces the occurrence of conflict. The conflict-reducing effect of CSR does not exceed the high conflict risk before CSR started. Abstract: Recent research finds that the opening of mines in Africa increases the risk of local protests and conflict. However, few empirical studies have analysed the effect of 'Corporate Social Responsibility' (CSR) of mining companies on conflicts in extraction areas. This study investigates the relationship between CSR payments and conflicts in African mining communities using econometric techniques. We create and explore a large dataset on CSR payments by 292 mining companies across 17 African countries and eight years. Our study finds that mining companies are more likely to engage in CSR activities when they are exposed to conflict in their areas of operation in previous years. Once conducted, CSR activities attenuate tensions. However, CSR does not lead to lower levels of conflict than in mining areas that have never received any CSR. The latter might be less in 'need' of CSR to manage operational risks in the first place. These findings support the view that mining companies engage in CSR activities to counter operational risks associated with local conflict, but that the effects are moderate.